Fractography analysis into low-C steel undergone through various destructive mechanical tests - Saurabh Dewangan; Senthil Kumaran Selvaraj; B Karthikeyan; Utkarsh Chadha; Prakrit Singhal; Partha Pratim Sarma; P Venkateshwar Raju; Uday Kumar; M Pradeep Kumar (Materials Research Express, 2022)
The present work deals with a critical fractographic analysis into low carbon (0.18%-C) steel samples which were used for three different mechanical tests: tensile test; shear test; and toughness test. These mechanical tests were performed in standard sized specimens as recommended by ASTM. In each category of test, there were two different specimens with different physical states according to heat treated conditions. First specimen was in ‘as received’ condition and another was annealed. For annealing, sample was first heated up to austenitic temperature and inserted inside the sand for slow rate of cooling. As these two categories of samples were undergone through destructive tests, the variation in fracture behaviour of the samples was analysed by FESEM, XRD. A significant variation in fractographic images could be observed in different heat-treated samples. Micro-pores, dimples, cleavage facet, peaks, valleys, and cave formation were observed in the samples.